3-methoxy aroylhydrazones – free radicals scavenging, anticancer and cytoprotective potency. (2nd November 2017) - Hristova-Avakumova, Nadya; Yoncheva, Krassimira; Nikolova-Mladenova, Boryana; Traykov, Trayko; Momekov, Georgi; Hadjimitova, Vera
ABSTRACT: Objective: This study aimed to determine the capability of newly designed 3-methoxy derivatives of salicylaldehyde benzoylhydrazone to influence the oxidative stress processes and to test their in vitro cytotoxicity. Methods: We have used chemiluminescent and spectrophotometric model systems containing different types of reactive oxygen species (OH ●, OCl ─ and O2 ─● ). The hydrazones effect on the viability of Hep-G2, HEK-293 and SH-SY5Y cell lines was determined via MTT assay. Results: The comparative analysis of the C50 values of the chemiluminescent investigation demonstrated moderate activity against the hydroxyl radicals (C50  > 50 μmol/L) and remarkable reactivity in the systems containing a superoxide radical and a hypochlorous anion (C50  < 3.7 μmol/L). Further experiments in the spectrophotometric system of UV-induced OH ● generation and consequent 2′-deoxyribose oxidative damage excluded the possibility of quenching effect and proved the direct interaction of the studied compounds with that generated in the system reactive oxygen species (ROS). The encapsulation of the studied derivatives into chitosan-alginate particles led to the protection and stabilization of their antioxidant activity as revealed by a one-month study using the ABTS ●+ method. The cytotoxic study revealed less pronounced effects against the non-malignant cell line (HEK-293) compared to Hep-G2 and SH-SY-5Y cells. Discussion: The incorporation of a hydroxyl group in the hydrazide part of a parent molecule which relates to better antioxidant effect in most of the studied systems is associated with higher IC50 values in all cytotoxicity experiments and relates to the cytoprotective effect against N-methyl-D-aspartate-induced excitotoxicity in SH-SY5Y human neuronal cells.